Dynamic analysis of unilateral harpoon-shift synchronizer for electric vehicles. (March 2021) - Mo, Wenwei; Walker, Paul D.; Tian, Yang; Zhang, Nong
Highlights: A new concept of unilateral Harpoon-shift synchronizer is presented for electric vehicles. Harpoon shift only requires a small and constant shift force for gear shifts. Harpoon shift relies on kinetic energy of relative motion to turn the guide ring. A detailed dynamic model is developed to capture the transients of the Harpoon-shift synchronizer. Speed difference significantly impacts the Harpoon-shift dynamic performance. Abstract: A novel unilateral Harpoon shift is developed as an alternative for conventional cone-type synchronizers used in electric vehicles equipped with multi-speed clutchless automated manual transmission (CLAMT), aiming to improve the gearbox's efficiency and performance. Harpoon shift can overcome the drawbacks of traditional synchronizers, including friction loss and wear, and simplify gearshift control. A detailed dynamic model of Harpoon shift is established to investigate the transients of the proposed synchronizer during engagement. Also, an experiment is performed to evaluate the engaging performance of Harpoon shift and validate the effectiveness of the model. Besides, the effects of rotating speed and speed difference on the torsional shock during engagement are analyzed quantitatively. Simulation and experimental results demonstrate distinct advantages of Harpoon shift over the conventional synchronizers.